The Impact of Fintech Peer-to-Peer Lending Investments on Public Financial Inclusion - Alfiana, Alfiana; Mulatsih, Listiana Sri; Widyantini, Dian; Meutianingrum, Farah Juniati; Afrizal, Afrizal (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The purpose of this study is to determine the impact of peer-to-peer lending fintech investments on public financial inclusion. This research approach collected data through a literature review, which involved reading literature from various sources, including books, reports, articles, and journals, employing both qualitative and deductive methods. The findings of this study suggest that peer-to-peer lending fintech investments have a positive impact on financial inclusion, including increased economic activity, enhanced financial literacy, and expanded investment opportunities. However, this system still faces various challenges, including the risk of default, data security concerns, a lack of education, and immature regulations. To overcome these challenges and strengthen its positive impact, collaboration between the government and platform providers is necessary to enhance rules, financial education, and digital literacy, as well as develop sharia-compliant and socially responsible products, so that peer-to-peer lending can become an integral part of an inclusive and sustainable financial system.